The Digital Subject - Claire, Larsonneur; Arnaud, Regnauld; Pierre, Cassou-Noguès; Sara, Touiza (La Grande Collection ArTeC, 2017)
Our societies have now gone almost fully digital, which is bound to impact the ways in which the self apprehends itself, constructs itself and takes part in society. This collective essay draws upon philosophy, logics, literature and media studies to explore a variety of responses to what is currently at stake in the recomposition of the subject through our daily digital experience. Attempting to chart the digital traces human beings leave behind them, in writing or in archives, it situates them in the larger political, economic and financial frame of our times.